2007
DOI: 10.1007/s10461-006-9204-5
|View full text |Cite
|
Sign up to set email alerts
|

Residential Status as a Risk Factor for Drug Use and HIV Risk Among Young Men Who Have Sex with Men

Abstract: There is growing behavioral and epidemiological evidence to suggest that young men who have sex with men (YMSM) are at high risk for becoming HIV-infected. Unfortunately, relatively little research has been conducted to examine the range of individual, social, and community-level factors that put these young men at increased risk. To address existing gaps in the literature, the Healthy Young Men's (HYM) Study was launched in Los Angeles to examine the range of factors associated with HIV risk and protective be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 59 publications
8
43
2
Order By: Relevance
“…41 Previous research has debated whether prior drug use among youth may predict homelessness or does homelessness serve as a predictor of drug use, and determining which is an antecedent to the other has been difficult to ascertain due to the crosssectional methods used in most of the studies of homeless youth. 10,42,43 Our results suggest that experiencing stigma relating to one's sexual orientation and ever being kicked out of one's home increase the risk of elevated marijuana use tremendously within groups of YMSM, regardless of their current housing status. Despite our cross-sectional design, there are sequential paths implicit in the model due to the temporal frames embedded in the measures: experience of sexual orientation-related stigma in the past, ever being kicked out of one's home, experiencing homelessness over the past 12 months, daily marijuana use during the past 90 days, and major depressive symptoms over the past 7 days.…”
Section: Discussionmentioning
confidence: 78%
“…41 Previous research has debated whether prior drug use among youth may predict homelessness or does homelessness serve as a predictor of drug use, and determining which is an antecedent to the other has been difficult to ascertain due to the crosssectional methods used in most of the studies of homeless youth. 10,42,43 Our results suggest that experiencing stigma relating to one's sexual orientation and ever being kicked out of one's home increase the risk of elevated marijuana use tremendously within groups of YMSM, regardless of their current housing status. Despite our cross-sectional design, there are sequential paths implicit in the model due to the temporal frames embedded in the measures: experience of sexual orientation-related stigma in the past, ever being kicked out of one's home, experiencing homelessness over the past 12 months, daily marijuana use during the past 90 days, and major depressive symptoms over the past 7 days.…”
Section: Discussionmentioning
confidence: 78%
“…[33][34][35] Emerging evidence demonstrates that improvements in housing status also contribute to reductions in HIV-related risk behaviors. [36][37][38][39][40][41][42] One study of more than 2,000 people found that at baseline, recent drug use, needle use, and "transactional" sex-exchanging sex for money, drugs, or other resources-were more common in homeless or marginally housed people than in those with stable housing. At six-to-nine-month follow-up, those who experienced an improvement in their housing status decreased their frequency of drug use, needle use, needle sharing, and unprotected sexual intercourse compared with people whose housing did not change.…”
Section: Stable Housingmentioning
confidence: 99%
“…6 With regard to sexual minority men, a Los Angeles-based cohort study found 17 % of participants had been forced to move from a family or friend's home because of their sexuality. 8 These data suggest that housing instability may manifest itself in many forms and consequently may produce a range of physical and mental health outcomes. Homeless SMY have particularly high rates of HIV risk behaviors, suicidality, depression, physical victimization, and substance abuse problems.…”
Section: Introductionmentioning
confidence: 99%